Critical review of corrosion protection by cold spray coatings - Hassani-Gangaraj, S. M.; Moridi, A.; Guagliano, M. (Surface engineering, 2015)
Successful deposition of variety of materials by cold spray provides the opportunity to tailor a wide range of coating/substrate systems with specific functions for different applications. The aim of this paper is to present a critical review of cold spray for corrosion protection. Application of cold spray to provide superior corrosion resistance by depositing more noble materials, formation of passivation layer, and cathodic protection is reviewed. State-of-the-art on cold spray deposition for corrosion mitigation is summarised. Special attention is given to assess the effect of cold spray parameters and conditions on the resultant corrosion performance. The effects of deposition temperature/pressure, particle size, coating thickness, carrier gas, post-treatment, and co-deposition of metals and ceramic particles on corrosion behaviour are discussed. Specific industrial applications of cold spray against corrosion are presented by a few examples in various fields such as biomedical, naval, electronics and hot corrosion protection. The review is concluded with a designated section to critically discuss the 'path forward', and propose new avenues for further research and developments.